SIMPLE ACCOUNTING FOR SURABAYA'S SMEs - Mohammad Ghofirin; Endah Tri Wahyuningtyas (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
Small and Medium Enterprises (SMEs) have been recognize as very strategic and important not only for economic growth but also for equitable distribution of income. So far, SMEs are still facing the problem of low-quality human resources, including in terms of business accounting. This Community Service (Pengmas) aims to increase the understanding of the business community in preparing SMEs financial reports using simple accounting techniques. This community service was attended by women in Family Welfare Empowerment or Pembinaan Kesejahteraan Keluarga (PKK) who have SMEs in Wonokromo Sub-district, Surabaya, totaling 79 people. The service method used is in the form of education where the partner group (PKK) is given simple accounting knowledge. The results of community service show that the understanding of PKK women in Wonokromo Sub-district, Surabaya regarding simple accounting for SMEs has increased.